Complete mitochondrial genome characterization and phylogenetic analyses of the main vector of Crimean-Congo haemorrhagic fever virus: Hyalomma marginatum Koch, 1844 - Ciloglu, Arif; Ibis, Osman; Yildirim, Alparslan; Aktas, Munir; Duzlu, Onder; Onder, Zuhal; Inci, Abdullah (Elsevier Gmbh, 2021)
The Mediterranean tick, Hyalomma marginatum, is the most important vector of Crimean-Congo haemorrhagic fever virus and several pathogens that cause animal and human diseases and economic losses to livestock production. Given the medical and veterinary importance of this tick species, we sequenced and characterized its mitochondrial genome (mitogenome) for the first time. We designed two new primer sets and combined longrange PCR with next generation sequencing to generate complete mitogenomes with deep coverage from 10 H. marginatum adults. The mitogenomes contained 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal subunits, two control regions, and three tick-box motifs. The nucleotide composition of the H. marginatum mitogenomes were A+T biased (79.76%) and exhibited negative AT- and GC- skews across most PCGs. All PCGs were initiated by ATK codons and two truncated termination codons were seen in the COX2 and COX3 genes. All tRNAs exhibited typical cloverleaf structures, except for tRNACys and tRNASer1. A total of 62 polymorphic sites defined ten unique haplotypes. Phylogenetic analyses based on the 13 PCGs of 56 tick species revealed that four Hyalomma species (H. marginatum, H. asiaticum, H. rufipes, and H. truncatum) formed a monophyletic clade with strong support. The results of this study provide a comprehensive resource for further studies on the systematics, population genetics, molecular epidemiology, and evolution of ticks.
Keywords: Hyalomma marginatum; Mitogenome; Genetic diversity; Phylogeny; Tick Ixodida